Determine the Level of IL-17 in People Recovering from Viral Infections of the Respiratory System - Zahraa Khalid Al-Kheroo; Khalid N. Al-Kheroo; Mahmood Abd Al Jabbar Al-Tobje (Cam & Sakura Medical Journal)
Objective: Numerous illnesses, such as bacterial and viral infections, affect the respiratory system. Since no known therapy for viruses directly influences health, viral infections are typically more deadly than bacterial ones. The study aimed to ascertain the degree of many immunological markers in patients recovering from viral respiratory infections. The amounts of these indicators were ascertained using the ELISA technique. Material and Methods: The study includes 74 sample collections from June to September (2023), including 28 males and 46 females, aged over 18. Blood samples, overall, were taken. The study was conducted in the Research Laboratory of the Department of Biology, College of Science, University of Mosul. Seventy-four individuals were involved in the study; forty-six of them were recovering from being severe acute respiratory syndrome coronavirus-2 positive (after 6 months), and twenty-eight were not. Results: The findings revealed highly variable levels of interleukin-17 (IL-17), immunoglobulin M (IgM), and immunoglobulin G (IgG) between the patient samples and the control samples. While the IgG level was higher in the first age group (20-40 years), the levels of both IgM and IL-17 were higher in older ages (41-60 years). The levels of immune markers were higher in females than in males, with IL-17, IgG, and IgM reaching 133.3 pg/mL, 1707.9 ng/mL, and 56.8 ng/mL, respectively. Conclusion: According to the current study, the parameters measured in coronavirus disease-2019 recovery participants after six months were higher than those in control samples.